An unusual phenotype of MEN1 syndrome with a SI-NEN associated with a deletion of the MEN1 gene. (1st April 2016) - Manoharan, Jerena; Lopez, Caroline L; Hackmann, Karl; Albers, Max B; Pehl, Anika; Kann, Peter H; Slater, Emily P; Schröck, Evelin; Bartsch, Detlef K
Summary: We report about a young female who developed an unusual and an aggressive phenotype of the MEN1 syndrome characterized by the development of a pHPT, malignant non-functioning pancreatic and duodenal neuroendocrine neoplasias, a pituitary adenoma, a non-functioning adrenal adenoma and also a malignant jejunal NET at the age of 37 years. Initial Sanger sequencing could not detect a germline mutation of the MEN1 gene, but next generation sequencing and MPLA revealed a deletion of the MEN1 gene ranging between 7.6 and 25.9 kb. Small intestine neuroendocrine neoplasias (SI-NENs) are currently not considered to be a part of the phenotype of the MEN1-syndrome. In our patient the SI-NENs were detected during follow-up imaging on Ga68-Dotatoc PET/CT and could be completely resected. Although SI-NENs are extremely rare, these tumors should also be considered in MEN1 patients. Whether an aggressive phenotype or the occurrence of SI-NENs in MEN1 are more likely associated with large deletions of the gene warrants further investigation. Learning points: Our patient presents an extraordinary course of disease. Although SI-NENs are extremely rare, these tumors should also be considered in MEN1 patients, besides the typical MEN1 associated tumors. This case reports indicate that in some cases conventional mutation analysis of MEN1 patients should be supplemented by the search for larger gene deletions with modern techniques, if no germline mutation could be identified by Sanger sequencing.